Role of a Semiotics-Based Curriculum in Empathy Enhancement: A Longitudinal Study in Three Dominican Medical Schools - San-Martín, Montserrat; Delgado-Bolton, Roberto; Vivanco, Luis (Frontiers in Psychology, 2017)
Background: Empathy in the context of patient care is defined as a predominantly cognitive attribute that involves an understanding of the patient’s experiences, concerns, and perspectives, combined with a capacity to communicate this understanding and an intention to help. In medical education, it is recognised that empathy can be improved by interventional approaches. In this sense, a semiotic-based curriculum could be an important didactic tool for improving medical empathy. The main purpose of this study was to determine if in medical schools where a semiotic-based curriculum is offered, the empathetic orientation of medical students improves as a consequence of the acquisition and development of students’ communication skills that are required in clinician-patient encounters. Design: This quasi-experimental study was conducted in three medical schools of the Dominican Republic that offer three different medical curricula: i) a theoretical and practical semiotic-based curriculum; ii) a theoretical semiotic-based curriculum; and iii) a curriculum without semiotic courses. The Jefferson scale of empathy (JSE) was administered in two different moments to students enrolled in pre-clinical cycles of those institutions. Data was subjected to comparative statistical analysis and logistic regression analysis. Results: The study included 165 students (55 male and 110 female). Comparison analysis showed statistically significant differences in the development of empathy among groups (p<0.001). Logistic regression confirmed that gender, age, and a semiotic-based curriculum contributed towards the enhancement of empathy. Conclusions: These findings demonstrate the importance of medical semiotics as a didactic teaching method for improving beginners’ empathetic orientation in patients’ care.